Assessment of forest revenue system in Kogi State (2011)
Low and arbitrary review of forest charges encourage waste and poor harvesting practices resulting in underdevelopment of forest resources. The study therefore assessed the type, value and changes in the value of forest charges in Kogi State between 1991 and 2009. Data on forest charges between 1991 when the state was created and 2009 were collected from the Forestry Service of Kogi State. GDP deflator was used to convert the forest charges in each year under study to real or constant values thereby compensating for the effect of inflation on the value of forest charges. Average annual change in the forest charges was calculated for the period under study while sensitivity analysis was carried out to determine the current (2009) equivalent value of the base year (1991) value of forest charges.The State Forestry Service (SFS) operates 35 different charges from eight groups of charges with the exception of Forestry Trust Fund. The SFS started operating 11 of the 35 charges since 1991 when the State was created and these 11 forest charges have been reviewed twice, one in 1997 and the other in 2004. Another 11 different charges were introduced in 1997, all of which were reviewed once in 2004. The remaining 11 other various charges were introduced in 2004 and are yet to be reviewed. Three methods - residual or stumpage valuation; calculation of the volume of timber transported from the forest; as well as consultation and negotiation- are used in determining the forest charges. The difference between the average annual change in the nominal value and the real current value is relatively high (16.06% to 17.68%) for the forest charges whose base year is 1991. Forest charges whose base year is 1996/1997 have lower differences (9.08% to 11.90%) while those whose base year is 2004 have difference of 7.38%. In order to have a better forest revenue system in Kogi State, setting of forest charges should be primarily based on the market prices of the products coupled with consultation with the stakeholders. The review of the charges which should be done more regularly such as once in three years should be adjusted for inflation